2021
DOI: 10.3390/genes12091418
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Microneme Protein 2 and Surface Antigen 1 of Eimeria tenella

Abstract: Avian coccidiosis is a disease caused by members of the genus Eimeria. Huge economic losses incurred by the global poultry industry due to coccidiosis have increased the need for cost-effective and easily available recombinant vaccines. Microneme protein 2 (MIC2) and surface antigen 1 (SAG1) of E. tenella have been recognised as potential vaccine candidates. However, the genetic diversity of the antigens in field isolates, which affects vaccine efficacy, has yet to be largely investigated. Here, we analysed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…However, further studies based on larger numbers of E. tenella field isolates from different geographical areas are needed to determine genetic heterogeneity. Meanwhile, it is necessary to evaluate the protective efficacy of EtROP17 showing amino acid changes, as genetic polymorphisms of vaccine candidates may affect protective efficacy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies based on larger numbers of E. tenella field isolates from different geographical areas are needed to determine genetic heterogeneity. Meanwhile, it is necessary to evaluate the protective efficacy of EtROP17 showing amino acid changes, as genetic polymorphisms of vaccine candidates may affect protective efficacy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low antigenic diversity has been reported for genes encoding for E. tenella surface antigens such as IMP-1, AMA1, SAG1, and MIC2 [ 108 , 131 , 132 ], a desirable feature for their inclusion in vaccines formulations since a high variability could impair its effectivity in different regions. Low variability for a protein is usually related to an essential function.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the genetic diversity of this antigen—along with EtMIC2—was analysed among 231 E. tenella- positive isolates from China and India, and compared with Korean isolates. The study demonstrated that this antigen is highly conserved since little variability was found among isolates [ 108 ]. Etsag1 in these isolates was classified into four different haplotypes and showed limited amino acid polymorphism.…”
Section: Surface Proteins Of Eimeria Sppmentioning
confidence: 99%
“…The expression of SAG is differentially regulated between oocyst/zygotes and second-generation cleavage stages, with only one being specifically expressed in the zygotes, a few in both stages, and most in the second generation cleavage ( Tabares et al, 2004 ), with the SAG B gene being specifically expressed in the second-generation cleavage peak expression in the second generation of cleistogamy. In recent years, many researchers have investigated the immunogenicity of SAG proteins, such as SAG1 ( Vo et al, 2021 ), SAG2, SAG4 ( Zhao et al, 2020b ), SAG6, SAG15 ( Geng et al, 2022 ), SAG16, SAG22, SAG23 ( Song et al, 2021 ; Zhao et al, 2021 ), among which SAG1, SAG4, SAG15, and SAG22 have candidate antigenic genes to be anticoccidial vaccines. In general, protective antigens will prefer proteins expressed in the intracellular phase or in the metabolically active phase of the worm, whereas SAG22 belongs to the SAG B gene, which is capable of efficient expression in the second generation of cleavers.…”
Section: Discussionmentioning
confidence: 99%